The effects of exercise training for eight weeks on immune cell characteristics among breast cancer survivors - Arana Echarri, Ainhoa; Struszczak, Lauren; Beresford, Mark; Campbell, John P.; Thompson, Dylan; Turner, James E. (Frontiers in Sports and Active Living, 2023)
This study examined the effects of exercise training for 8 weeks on blood immune cell characteristics among 20 breast cancer survivors (age 56 ± 6 years, Body Mass Index 25.4 ± 3.0 kg.m2) within two years of treatment. Participants were randomly allocated to a partly-supervised or a remotely-supported exercise group (n=10 each). The partly supervised group undertook 2 supervised (laboratory-based treadmill walking and cycling) and 1 unsupervised session per week (outdoor walking) progressing from 35-50 mins and 55-70% V̇O2max. The remotely-supported group received weekly exercise/outdoor walking targets (progressing from 105-150 mins per week 55-70% V̇O2max) via weekly telephone calls discussing data from a fitness tracker. Immune cell counts were assessed using flow cytometry: CD4+ and CD8+ T cells (Naïve, NA; Central memory, CM; and Effector cells, EM and EMRA; using CD27/CD45RA), Stem cell-like memory T cells (TSCMs; using CD95/CD127), B cells (plasmablasts, memory, immature and naïve cells using CD19/CD27/CD38/CD10) and Natural Killer cells (effector and regulatory cells, using CD56/CD16). T cell function was assessed by unstimulated HLA-DR expression or interferon gamma (IFN-γ) production with Enzyme-linked ImmunoSpot assays following stimulation with virus or tumour-associated antigens. Total leukocyte counts, lymphocytes, monocytes and neutrophils did not change with training (p>0.425). Most CD4+ and CD8+ T cell subtypes, including TSCMs, and B cell and NK cell subtypes did not change (p>0.127). However, across groups combined, the CD4+ EMRA T cell count was lower after training (cells/µL: 18 ± 33 vs 12 ± 22, p=0.028) and these cells were less activated on a per cell basis (HLA-DR median fluorescence intensity: 463 ± 138 vs 420 ± 77, p=0.018). Furthermore, the partly-supervised group showed a significant decrease in the CD4+/CD8+ ratio (3.90 ± 2.98 vs 2.54 ± 1.29, p=0.006) and a significant increase of regulatory NK cells (cells/µL: 16 ± 8 vs 21 ± 10, p=0.011). T cell IFN-γ production did not change with exercise training (p>0.515). In summary, most immune cell characteristics are relatively stable with 8 weeks of exercise training among breast cancer survivors. The lower counts and activation of CD4+ EMRA T cells, might reflect an anti-immunosenescence effect of exercise.